(untitled) (Pain medicine, 2019)
Objective: To evaluate the efficacy of the therapy performed 12 months after initiation of treatment in patients with osteoarthrosis (OA) combined with hypertension (GC) with treatment with meloxicam at a dose of 7.5 mg/day and 80 mg/day and 160 mg/day "difores". Materials and methods: under observation in outpatient settings, there were 60 patients on OA 1–2 stages, in combination with GC 2 degree, 2–3 degrees. The average age of patients with OA was 64.4 ± 7.5 years, patients with OA in combination with GC – 62.13 ± 8.2 years – 41 (68.3 %) women and 19 (31.7 %) men. Duration of the disease was in patients with OA – (9.66 ± 4.7) years, in patients with a comorbidity of OA and GC – (9.4 ± 6.0) years, respectively. To perform the research tasks, all patients were divided into 3 groups of 30 patients in each of them. The first group – patients with OA without GC, the second one – patients with a combination of OA and GC, the third group of comparison contained practically healthy persons. All patients complained of pain syndrome of varying degrees of severity. Patients of the first two groups received methoxy at a dose of 7.5 mg per day as baseline therapy; meloxicam and antihypertensive drug "diforsi" at a dose of 80 mg per day – patients in the second group were taken, but in 29 % of patients in this group "diormos" was prescribed at a dose of 160 mg. Duration of treatment was 12 months. A general clinical examination was performed inall patients at the beginning of the study, and after treatment: general blood tests, office blood pressure measurements, electrocardiography (ECG), daily blood pressure monitoring (DMAT), radiography of the knee joints. Results: • According to the results, the positive effect of using meloxicam caused a significant decrease in the severity of pain in the first and second groups according to the visual analog scale (VAS): (by 27.8 % and 29.8 % respectively, p < 0.05) and the Lequesne index (respectively 27.1 % and 30.9 %, p < 0.05). • Also, the analgesic and anti-inflammatory effect of meloxicam and its positive effect on the clinical course of OA were revealed: joint pain decreased, functional capacity in-creased, general well-being and quality of life of patients improved.